Meningkatan Keterampilan Berbicara dengan Bercerita melalui Media Audio Visual VCD pada Anak Kelompok B PAUD Dharma WanitaKabupaten Bengkulu Tengah - Vivi Umiya Lestari; Sri Saparahayuningsih; Yulidesni Yulidesni (Universitas Bengkulu, 2017)
The problem in this research is how the application of VCD audio visual media can improve speaking skill in children of group B PAUD Dharma Wanita of Central Bengkulu Regency. This study aims to improve children's speaking skills by telling stories through VCD audio visual media. This research is a classroom action research. The study was conducted in two cycles with three meetings in each cycle. Subjects in this study were children group B which amounted to 14 children consisting of 10 boys and 4 girls. Technique of collecting data is done through observation, while data analysis using formula mean and mastery learn. The results of this study prove that through VCD audio visual media can improve children's speaking skills from the average in cycle 3.27 with the criteria enough to the average in the second cycle 4.25 with good criteria. This increase is due to the use of VCD audio visual media by focusing on vocabulary mastery, articulation, and sentence structure. This study is not suitable for quiet children and has a short concentration of power, therefore it is suggested to the next researcher to continue the study with regard to it.